The Black Android, Janelle Monáe and Crossover Stardom: Race and Technology On-screen - Liam Rogers (Film-Philosophy)
Artificial people, far from embodying the false promise of a post-racial future, come to be inscribed with signifiers of race across science fiction film and television. However, like Western philosophy’s theorisation of technology, on-screen imaginations of artificial people are overwhelmingly white. With the help of critical race theory and critical philosophies of race, this article explores what it means for an artificial person to be Black. It brings a comprehensive account of the racialisation of technology, both off- and on-screen, into conversation with the work of Afrofuturist musician Janelle Monáe. Together, these complementary frameworks form the basis from which to consider Monáe’s performance as a Black android in the television series Electric Dreams (2017–18) episode “Autofac” (2018), adapted from the work of Philip K. Dick. Reading “Autofac” through Monáe’s crossover stardom enables negotiated cultural tensions of race and technology to emerge from a text that opts out of explicitly addressing the issue of race. In doing so, this article elucidates how film and television draw upon, contribute to and actively shape the inextricability of technology and race.